Effect of isovalent substitution and Quenching on the Transition Temperature of (Bi1-xPbx)2(Sr1-yBay)2Ca2Cu3O10+δ - AL-Shakarchi, E. KH. (Iraqi Journal of Physics, 2009)
A high Tc superconductor with a nominal composition (Bi1-xPbx)2(Sr1-yBay)2Ca2Cu3O10+δ for (0 £ x £ 0.5) and (0 £ y £ 0.5) was prepared by a solid state reaction method. The effect of the substitution of Pb for Bi and Ba for Sr and quenching temperature on the superconductivity has been investigated to obtain the optimum conditions for the formation and stabilization of the high Tc phase (2223). The results showed that the optimum sintering temperature for the pure composition is equal to 875°C and the sintering time is equal to 240h with heating and cooling rate of 60°C/h . Our results indicated that a small amount of (Ba = 0.1) could raise the transition temperature (Tc), but enhancing Ba to 0.4 has raised the resistivity and the behavior of the composition converted to semiconductor and ultimately for the composition that has (x = 0.4, y = 0.5) was an insulator. The best value of (Tc = 122 K) is for the composition that has x = 0.2, y = 0.1.On the other side for Ba free samples increasing of lead content up to 0.3 has rise the transition temperature (Tc = 116 K) but more increases to (0.4, 0.5) causes a decrease in Tc. The effect of quenching temperature Tq on the transition temperature Tc of the (Bi1- xPbx)2(Sr1-yBay)2Ca2Cu3O10+δ was also investigated .